KONSEP PEMBELAJARAN BAHASA ARAB DENGAN PENDEKATAN POSITIVE MENTAL ATTITUDE - Taubah, Miftachul; Aisyatul Hanun (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
Learning Arabic is often challenging, especially for students without prior knowledge. This article employs a qualitative method with a literature review approach to investigate the effectiveness of Positive Mental Attitude (PMA) in Arabic language learning. PMA, as a humanistic approach, aims to motivate students, enhance their enthusiasm for learning, and boost their confidence in facing learning challenges. Additionally, PMA helps reduce stress and anxiety, creates a positive classroom environment, and strengthens social relationships among students. The study's findings indicate that PMA supports perseverance and a never-give-up attitude, which overall improves students' language skills and long-term learning experiences. In conclusion, the PMA approach has great potential in facilitating a more effective and enjoyable Arabic language learning process.